Training For Teachers To Increase Student Competency Physics Lesson In Learning Through Media Animation Multimedia In SMP Negeri 9 Palembang - rusdi efendi (Annual Research Seminar (ARS), 2016)
PHYSICAL subjects in SMP / MTs aimed at one of them so that students have the ability to develop an understanding of the wide variety of natural phenomena, concepts and principles of PHYSICS useful and can be applied in everyday life. To achieve these objectives required numerous attempts via innovations as learning strategies, especially by teachers who can provide direct experience with students so that students acquire learning through the learning process. One way that can be utilized is through the medium of learning. Medium of learning is something (to tools, materials, or state) that is used as an intermediary for communication in the learning activities. There are six basic categories of media, namely: text, audio, visual, video, manipulative (objects), and people. Macromedia Flash is a graphics animation program that can be used to create an interesting learning media. Macromedia Flash allows animators to create interactive and expressive projects that can be displayed in a pretty good quality on a variety of devices so that students will be interested in the material presented.